EVALUATION OF RATIONAL USE OF AMLODIPINE AND CAPTOPRIL IN TYPE 2 DIABETES MELLITUS PATIENTS WITH COMORBIDITIES AT TANGERANG DISTRICT GENERAL HOSPITAL - Ahsan Yusma; Rizki Amalia Syafitri; Mutawalli Sjahid Latief; Febri Hidayat (Institut Sains dan Teknologi Al-Kamal, 2025)
Rational use of antihypertensive drugs is essential for patients with Type 2 Diabetes Mellitus (T2DM) with comorbidities to optimize therapeutic efficacy and minimize adverse drug reactions. This study aimed to evaluate the appropriateness of antihypertensive therapy in outpatient BPJS T2DM patients at RSU Tangerang District. A descriptive retrospective study was conducted on 80 BPJS T2DM patients with comorbidities who received captopril or amlodipine from January to June 2021. Data were collected from medical records and analyzed for appropriateness regarding contraindications, indications, drug selection, and dosage according to clinical guidelines including JNC VII/VIII, ACC/AHA, Pharmaceutical Care, and PIONAS. All patients received medications without contraindications, resulting in a 100% appropriateness rate. Specifically, 68.8% of patients received captopril and 31.3% received amlodipine appropriately. All indications and drug selections were fully aligned with clinical guidelines, and dosing was correct for all patients: captopril 12.5 mg in 14 cases (17.50%) and 25 mg in 41 cases (51.25%), amlodipine 5 mg in 19 cases (23.75%) and 10 mg in 6 cases (7.50%). Antihypertensive therapy in BPJS T2DM patients at RSU Tangerang District was rational and fully adherent to clinical guidelines, ensuring patient safety and therapeutic efficacy. The study was limited to two drugs and outpatient care; therefore, future research should include additional antihypertensive medications and care settings to generalize the findings.